Managerial challenges to realizing IT shared services in a public university. Issue 1 (18th March 2019) - Olsen, Timothy; Welke, Richard
Abstract : Purpose: Many governments and public organizations are turning to shared service arrangements to decrease costs while increasing service levels. This paper aims to elucidate the fine-grained challenges managers face as they adjust to working under a shared service arrangement. Design/methodology/approach: A two-year longitudinal ethnographic field study followed the IT shared service transformation process at a large public university. Meeting observations, emails, documents and interviews were used in the qualitative analysis. Findings: The research identifies 11 challenges faced by management undergoing a transition to shared services. The authors use a taxonomy of management challenges based on the organizational perspectives literature (Knol et al., 2014) to organize the challenges and relate them to prior literature. Research limitations/implications: The novel findings include the importance of changing organizational culture, balancing dual interests of cost and customer focus, establishing a sense of urgency and achieving process standardization through practicing when adopting a shared service arrangement. The results from a single case study may not by generalizable to other organizations. Originality/value: This study provides a nuanced and fine-grained understanding of the managerial challenges of adopting IT-shared services. This unique longitudinal data set describes in nuanced detail the challenges faced by frontline managers.